2008
DOI: 10.1007/s00592-008-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of streptozotocin-induced oxidative stress in hepatic and intestinal tissues of wistar rat by methanolic-garlic extract

Abstract: Diabetes is a major socio-economical burden with serious health consequences. The reactive oxygen species generated in this pathology alters the internal milieu of the cellular systems paving way to metabolic disorders. In the present investigation garlic's dose-dependent protective action against streptozotocin (STZ)-induced oxidative stress in hepatic and intestinal tissues has been studied. Methanolic garlic extract scavenged the DPPH radical with an IC(50) of 424 +/- 4.4 microg/ml proving its efficient ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…1, consumption of garlic significantly decreased hepatic lipid peroxides compared with the control group, suggesting that garlic also showed antioxidant effect in vivo . This finding was in agreement with the results of previous studies which reported that injection of aqueous garlic extract (500 mg/kg) increased total serum antioxidant levels (Drobiova et al, 2009) and incubation of methanol garlic extract (500 mg/kg) decreased hepatic TBARS levels in STZ-treated diabetic rats (Kanth et al, 2008). In addition, we found that aged black garlic was more effective in reduction of hepatic TBARS levels than garlic.…”
Section: Discussionsupporting
confidence: 93%
“…1, consumption of garlic significantly decreased hepatic lipid peroxides compared with the control group, suggesting that garlic also showed antioxidant effect in vivo . This finding was in agreement with the results of previous studies which reported that injection of aqueous garlic extract (500 mg/kg) increased total serum antioxidant levels (Drobiova et al, 2009) and incubation of methanol garlic extract (500 mg/kg) decreased hepatic TBARS levels in STZ-treated diabetic rats (Kanth et al, 2008). In addition, we found that aged black garlic was more effective in reduction of hepatic TBARS levels than garlic.…”
Section: Discussionsupporting
confidence: 93%
“…A broad range of antioxidant properties have been attributed to allicin, including direct scavenging of free radicals, maintenance of glutathione and the endogenous antioxidant redox balance, as well as the enhanced expression of the antioxidant enzymes glutathione peroxidase, glutathione reductase, SOD and CAT ( 13 ). Furthermore, allicin can suppress the production of certain inflammatory cytokines that have been implicated in the pathogenesis of diabetic complications, including tumor necrosis factor-α and transforming growth factor-1 ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Chinese herbal medicine, garlic has been used to treat a range of diseases for thousands of years. Allicin is one of the main active components in garlic and exerts several therapeutic effects, such as promoting insulin sensitivity ( 6 , 7 ), decreasing blood glucose levels ( 8 , 9 ), regulating lipid metabolism ( 10 , 11 ), reducing homocysteine levels ( 12 ), attenuating superoxide production ( 13 ) and limiting inflammation and fibrogenesis. Given the role of oxidative stress within the etiology and pathogenesis of diabetic complications, the present study utilized an in vitro model of diabetes-associated oxidative stress using aortic endothelial cells cultured under high-glucose/hypoxic conditions to clarify the possible mechanism of allicin on diabetic macrovascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also reveal the beneficial effects of garlic or its preparations in combating various diseases. Hypo-lipidaemic, anti-atherosclerotic, anticoagulant, antidiabetic, antihypertensive, antimicrobial, anticancer, antidote, hepatoprotective, and immunomodulatory activities of garlic are now well- established from animal and human studies ( Rajani Kanth et al, 2008 ). The salutary effects of garlic in Type-I and Type-II diabetes are also well established ( Padiya et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%